Lattice numerical study of qq system near to the deconfinement phase transition - Chagdaa, Sodbileg; Galsandorj, Enkhtuya; Laermann, Edwin; Purev, Battogtokh (Scientific transaction of the National University of Mongolia. Physics, 2022)
We study the profiles of the flux tube between a static quark and an antiquark in quenched SU(2) lattice gauge theory at temperatures around the deconfinement phase transition. The physical width of the flux tube and the string tension have been determined from the transverse profiles and the potential, respectively. Exploiting the computational power of a GPU accelerator in our flux tube investigation, we achieve a much higher statistics through which we can increase the signal to noise ratio of our observables in the simulation. This has allowed to investigate larger lattices as well as larger separations between the quarks than in our previous work. The improved accuracy gives us better results for the width and the string tension. The physical width of the flux tube is increasing with the temperature up to around Tc while keeping its increasing dependence on the separation. The string tension results have been compared for two different sizes of the lattice. As the lattice becomes larger and finer together with the precision improved, the temperature dependent string tension tends to have smaller value than the previous one.